RANCANG BANGUN APLIKASI VIRTUAL REALITY LABORATORIUM FAKULTAS TEKNIK UNIVERSITAS TANJUNGPURA - Melky, Florensius (Jurusan Informatika Universitas Tanjungpura, 2015)
ABSTRACT - Virtual Reality is atechnology that makes people as if can beinteract with an environment and see thereal shape of three-dimensional (3D) withthe computer device, and obtain theinformation from the object in laboratoriesof Engineering Faculty of TanjungpuraUniversity. The laboratories are growingalong with the development of theEngineering Faculty. The studentscandidate needed a web-based applicationthat can be directly help students andpublic in finding out the information aboutthe Engineering Faculty through the realpictures of the laboratories. Thisapplication was designed for public byusing various testing namely testing ofvalidity and testing of the questionnaireusing Likert Scale. The value result ofvalidity testing by three experts consistedof three aspects. The first aspect is contentaspect. It was 79.99; the second istechnical aspects. It was 82.91 and thethird is presentation aspects; it was 79.99.The mean score was 80.89. It can beconcluded that the results of validationapplication by three experts categorizedinto good. The questionnaires weredistributed for test user permission andadmin. Then the results of datainterpretation were showed in Likert Scale.From 35 user’s permissions respondents,the value was 49.4 categorized into verygood. From 7 admins respondents, thevalue was 28.83 categorized into excellent.From these tests, it can be concluded thatthe Application of Virtual RealityLaboratory of the Engineering Faculty ofTanjungpura University (Virlab) wasfeasible to be implemented.